Pharmacological Treatment of Bone Loss - Pang, Rui; Xia, Weibo (Current Pharmaceutical Design, 2017)
Bone loss is common in clinical practice, such as health assessment of postmenopausal women, treatment of tumor metastasis, side-effects of glucocorticoids, and skeletal manifestations of inflammatory diseases. The imbalance of remodeling between bone resorption and bone formation, the pathophysiological basis of bone loss, increases bone fragility. The treatment of bone loss is mainly carried out from the treatment of osteoporosis. There are various pharmacological therapies for bone loss, which will be introduced in 3 aspects, including antiresorptive agents, anabolic agents and new medications. Each kind of medication has its advantages, shortcomings and side-effects. Antiresorptive agents are widely applied in the treatment of bone loss, but can lead to overall decrease of bone turnover rate. Anabolic agents, mainly PTH, are usually combined with other anti-resorptive drugs, and PTHrP might be a promising pure anabolic agent for osteoporosis. In recent years, some novel therapies have been raised and tested in clinical trials which can be promising choices available for osteoporosis treatment. Future drug targets will mainly come from RANK-RANKL-OPG system and Wnt/β-catenin signaling pathway., and the pre-existing drugs could be explored in new patterns.
Keywords: osteolytic bone metastases